Studies on protozoan parasites in angwan rogo, Jos-North Local Government of Plateau State, Nigeria (2014)
A study was carried out on the incidence and spread of intestinal protozoan infections in the residents of Angwan Rogo Village in Jos-North Local Government Area of Plateau State, Nigeria. Faecal samples were collected from 686 residents and examined using direct smear and concentration techniques. Residents examined were between the ages of below 15 years and above and were drawn from five divided units of the study area. Results of the study showed generally low infection rates of 22.30%, 2.33%, 4.96%, and 2.77% for Entamoeba histolytica, Giardia lamblia, Balantidium coli and Entamoeba coli respectively. Infection rates for residents of different age groups showed little variation in the different parts of Angwan Rogo.There were cases of mixed infections with Entamoeba histolytica in most cases .Socio-economic factors such as types of toilets used and the personal hygiene appeared to have limited effects on the observed parasitic infection rates. Preventive measures to enhance control of the infections are discussed.